Simulating molecules on a cloud-based 5-qubit IBM-Q universal quantum computer - S. Leontica (Nature Portfolio, 2021)
Quantum simulators are becoming an established method to help investigate and unpack the complexities of a many-body system and understand how it evolves over time. Here, using the 5-qubit IBM cloud computer the authors simulate the evolution of a protein complex and show that the energy-transfer behaviour is consistent with theoretical expectations.